Criminal arbitration as a modality of restorative justice appropriate to the human being - Ahomed Chávez, Omar Abraham (2011)
With the fall of the Berlin wall and globalization, the philosophy of the primacy of private initiative has been the axis on which law is developing. Within the criminal justice system, this has been expressed in the preponderance of an accusatory model where the judge no longer directs the investigation, but decides, and where the leading role in offering evidence belongs to the procedural subjects, called the Public Ministry, defense of the accused or the victim. However, these reforms are insufficient, since the primacy of private initiative progressively questions the need for state intervention in criminal conflicts, and such institutionalization of the primacy of private initiative cannot be carried out within the accusatory model, whatever it may be. of its forms, because it is alien to it, as Antonio García-Pablos de Molina clearly refers to, who maintains that "the accusatory model is based on the separation between judge and prosecution, equality between prosecution and defense, orality and publicity of the judgment...etc But the discretion of the criminal action (free accusation) and the agreement or negotiation, has nothing to do with that theoretical model (accusatory system), nor with the so-called "criminal process of parties", but with singular characteristics of the North American system and with the opportunity principle.